AB0220 Serum phosphatidylserine-specific phospholipase A1 (PS-PLA1) is increased in active systemic lupus erythematosus (SLE) and is correlated with disease activity. (23rd January 2014) - Sawada, T.; Nakamura, K.; Igarashi, K.; Shoji, A.; Kimura, E.; Hayashi, H.; Tahara, K.; Aoki, J.; Yatomi, Y.
Abstract : Background: Lysophospholipids (LPLs) such as lysophosphatidic acid (LPA) and lysophosphatidylserine (LPS) are lipid mediators with multiple biological roles including immuno-regulatory functions (1, 2). LPA and LPS are known to be produced by autotaxin (ATX) and phosphatidylserine-specific phospholipase A1 (PS-PLA1 ), respectively. Objectives: To predict the levels of these lysophospholipid mediators in plasma of systemic lupus erythematosus (SLE) patients, we determined the levels of PS-PLA1 and ATX in sera from SLE patients and assessed their relationship with disease activity. Methods: Serum levels of PS-PLA1 and ATX were determined by enzyme-linked immunoassay in 26 patients with active SLE before and after corticosteroid treatment (3, 4). Sera from 40 patients with active rheumatoid arthritis (RA) and 7 patients with systemic sclerosis (SSc) were used as disease controls. Disease activity and organ damage in SLE patients were assessed using the SLE Disease Activity Index (SLEDAI) and British Isles Lupus Assessment Group (BILAG) index. Results: Serum PS-PLA1 levels were significantly higher in patients with SLE than in controls, while serum levels of ATX were similar among all patients. In SLE patients, serum levels of PS-PLA1 were positively correlated with global SLE activity indices (SLEDAI and BILAG scores) and serum IgG levels, but negatively correlated with complement C3 levels. Regarding individual organ damage, PS-PLA1 serum levels were correlated with the BILAG score for general constitutional symptoms, the mucocutaneous system, and vasculitis. Furthermore, PS-PLA1 serum levels decreased after immunosuppressive treatment in SLE patients. Conclusions: Measurement of PS-PLA1 may be useful for the clinical evaluation of SLE as a novel biological marker. The association of elevated PS-PLA1 serum levels with SLE disease activity suggests that LPS generated from PS-PLA1 may be involved in the pathogenesis of SLE. References: Aoki J, Nagai Y, Hosono H, Inoue K, Arai H. Structure and function of phosphatidylserine-specific phospholipase A1. Biochim Biophys Acta 2002;1582(1-3):26-32. Nakanaga K, Hama K, Aoki J: Autotaxin–an LPA producing enzyme with diverse functions. J Biochem 2010, 148(1):13-24. Nakamura K, Igarashi K, Ohkawa R, Saiki N, Nagasaki M, Uno K, et al. A novel enzyme immunoassay for the determination of phosphatidylserine-specific phospholipase A(1) in human serum samples. Clin Chim Acta 2010;411(15-16):1090-4. Nakamura K, Igarashi K, Ide K, Ohkawa R, Okubo S, Yokota H, et al. Validation of an autotaxin enzyme immunoassay in human serum samples and its application to hypoalbuminemia differentiation. Clin Chim Acta 2008;388(1-2):51-8. Disclosure of Interest: None Declared